Anesthetic care during spinal fusion in a patient with Williams syndrome. - M. Gross; D. P. Martin; W. Samora; J. Klamar; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2020)
illiams syndrome, also known as Williams-Beuren syndrome, was originally described in 1961. Patients with Williams syndrome have several distinguishing characteristics, including dysmorphic facies, cognitive dysfunction, hypercalcemia in infancy, and distinctive emotional and behavioral traits. This complex genetic syndrome results from a microdeletion on chromosome 7 that involves approximately 28 genes including the elas- tin gene (ELN). This deletion of ELN has been linked to many of the common connective tissue manifestations of Williams syndrome including the characteristic cardio- vascular structural abnormalities. The associated ortho- pedic involvement including scoliosis and kyphosis fre- quently requires surgical intervention. We present a 12- year-old adolescent with Williams syndrome requiring anesthetic care for a posterior spinal fusion. Associated organ system involvement and its perioperative impact are discussed.